STRATEGIC EMPOWERMENT OF SMES THROUGH DIGITAL FINANCIAL LITERACY: A CROSS-BORDER ENGAGEMENT FRAMEWORK USING SME ACCOUNTING STANDARDS AND FINANCIAL TECHNOLOGY TO SUPPORT SDG 9 - Musyaffi, Ayatullah Michael; Suyono, Windy Permata; Anwar, Choirul; Perdana, Petrolis Nusa; Tek Wei, Andrew Saw; Kurniawan, Arief (International Journal of Engagement and Empowerment (IJE2), 2025)
Small and Medium Enterprises (SMEs) are essential contributors to economic development, especially in emerging countries. However, many SMEs lack the necessary knowledge and tools to manage their finances effectively, particularly through standardized and digital approaches. This community engagement initiative seeks to enhance the digital financial literacy of SMEs through a cross-border collaboration between State University of Jakarta (Indonesia) and University Malaysia Sabah. The program introduced a structured empowerment framework that integrates SME accounting standards—particularly Indonesia’s SAK EMKM—with financial technology applications to support accurate and timely financial reporting. The activities included virtual training and mentoring on financial literacy, the use of cloud-based accounting tools, and simplified financial reporting procedures. Evaluation results showed significant improvement in participants’ ability to record transactions, prepare basic financial statements, and use digital accounting tools independently. This project demonstrates that integrating localized SME standards with financial technology can strengthen SME resilience, promote innovation, and contribute to Sustainable Development Goal 9 (Industry, Innovation, and Infrastructure).